Integrated disaster recovery: Linking health care and disaster case management - Craig Van Dyke; Mary C. Comerio; William E. Seaman; Arrietta Chakos (University of California, Institute of Urban and Regional Development (IURD), 2014)
In long-term recovery from natural disasters, the federal government helps to rebuild infrastructure, but individuals face a chaotic and uncoordinated assembly of state and local programs, insurance coverage, and assistance from nongovernmental organizations. The Federal Emergency Management Agency and other organizations have utilized case management, which matches individual needs for housing, health care, employment, and education, etc. with appropriate resources, to coordinate disaster recovery. However, these efforts have had uneven results. Case management limitations include: inability to identify and locate all those in need, implementation barriers, inability to scale services for large urban disasters, and poor sustainability. Linking disaster recovery case management with health care organizations, especially those with pre-existing health care case management programs, is a practical, scalable and sustainable approach to integrating the many aspects of disaster recovery and is a way for building community resilience before and after disasters.
Keywords: 330